2015
DOI: 10.1037/abn0000043
|View full text |Cite
|
Sign up to set email alerts
|

A developmentally informed perspective on the relation between stress and psychopathology: When the problem with stress is that there is not enough.

Abstract: A common tenet of several prominent theories of stress and psychopathology (e.g., stress exposure) is that experiencing high rates of life stressors is associated with greater risk for negative mental health outcomes. Although there has been substantial empirical support for this position, another possibility that has received considerably less attention to date is that early life stressors may share a curvilinear rather than monotonic relation with psychological well-being. In what has been termed the “steeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
76
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(83 citation statements)
references
References 102 publications
5
76
1
Order By: Relevance
“…However, as family income increased, the negative association between household instability and emotional SR became smaller, suggesting that families with higher incomes may have other resources to buffer the potential impact of instability on the child’s development. 5 The relationship between emotional SR and negative life events was curvilinear, which is consistent with the notion that moderate exposure to adversity may be health-promoting or “steeling”, 10 but intense or frequent exposure to adversity may overwhelm a child’s adaptive functioning. These findings support the hypothesis that early-life chronic stress influences neurodevelopmental processes underlying SR functions.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…However, as family income increased, the negative association between household instability and emotional SR became smaller, suggesting that families with higher incomes may have other resources to buffer the potential impact of instability on the child’s development. 5 The relationship between emotional SR and negative life events was curvilinear, which is consistent with the notion that moderate exposure to adversity may be health-promoting or “steeling”, 10 but intense or frequent exposure to adversity may overwhelm a child’s adaptive functioning. These findings support the hypothesis that early-life chronic stress influences neurodevelopmental processes underlying SR functions.…”
Section: Discussionsupporting
confidence: 76%
“…Both a linear term and a quadratic term for negative life events were included to account for the possibility of a curvilinear relationship – high-levels of stress may lead to negative developmental outcomes, whereas moderate levels of stress may confer resilience to later stressors. 10 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results could be due either to selection and/or to prior exposures promoting resilience (Wilson et al, 2009). Both experimental animal studies (Liu, 2015) and observational human studies (Rutter, 2012) support the resilience possibility, although research showing that intervening psychopathology due to prior traumas mediates the association between trauma history and subsequent PTSD (Sayed et al, 2015) confirms that prior traumas are more likely to create vulnerability than resilience. Research on the ‘healthy warrior effect’ supports the selection possibility (Larson, Highfill-McRoy, & Booth-Kewley, 2008; Wilson et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a sample of adolescents with externalizing symptoms, Hinnant et al (2015) found that a physiological marker of reduced stress sensi tivity (low resting respiratory sinus arrhythmia) was associated with increased delinquency and drug use, but only in the context of harsh parenting, and primarily for boys. The concept of reduced stress sensitivity was also explored by Liu (2015). Drawing on diverse literatures, this theoretical article articulates the hypothesis that exposure to moderate levels of stress may inoculate, or "steel," the individual against future threats, whereas exposure to both low and high levels of stress may heighten reactivity to future threats.…”
mentioning
confidence: 99%